Pilot Ex Vivo and In Vitro Evaluation of a Novel Foley Catheter with Antimicrobial Periurethral Irrigation for Prevention of Extraluminal Biofilm Colonization Leading to Catheter-Associated Urinary Tract Infections (CAUTIs). (24th December 2019) - Vargas-Cruz, Nylev; Rosenblatt, Joel; Reitzel, Ruth A; Chaftari, Anne-Marie; Hachem, Ray; Raad, Issam
Abstract : CAUTI remains a serious healthcare issue for incontinent patients whose urine drainage is managed by catheters. A novel double-balloon Foley catheter was developed which was capable of irrigating the extraluminal catheter surfaces within the periurethral space between the urethral-bladder junction and meatus. The catheter has a retention cuff that is inflated to secure the catheter in the bladder and a novel irrigation cuff proximal to the urethral-bladder junction capable of providing periurethral irrigation from the urethral-bladder junction to the meatus. Uniform periurethral irrigation was demonstrated in an ex vivo porcine model by adding a dye to the antimicrobial urethral irrigation solution. An in vitro biofilm colonization model was adapted to study the ability of periurethral irrigation with a newly developed antimicrobial combination consisting of polygalacturonic acid + caprylic acid (PG + CAP) to prevent axial colonization of the extraluminal urethral indwelling catheter shaft by common uropathogens. The extraluminal surface of control catheters that were not irrigated formed biofilms along the entire axial urethral tract after 24 hours. Significant (p < 0.001 ) inhibition of colonization was seen against multidrug-resistant Pseudomonas aeruginosa (PA), carbapenem-resistant Escherichia coli (EC), and carbapenem-resistant Klebsiella pneumoniae (KB). For other common uropathogens including Candida albicans (CA), Proteus mirabilis (PR), and Enterococcus faecalis (EF), a first irrigation treatment completely inhibited colonization of half of the indwelling catheter closest to the bladder and a second treatment largely disinfected the remaining intraurethral portion of the catheter towards the meatus. The novel Foley catheter and PG + CAP antimicrobial irrigant prevented biofilm colonization in an in vitro CAUTI model and merits further testing in an in vivo CAUTI prevention model.